Diferensiasi Interaksi Sosial Antara Generasi Milenial dan Gen Z - Rahmadhani, Intan; Sari, Devi Mutiara; Novianti, Irma; Finalson, Ginanjar Hatta; Khoirunnisa, Salwa Amanda (CV. Supernova Office Stationary and Printing, 2024)
This article examines the differences in social interactions between the millennial and Gen Z generations. Through a scientific approach, this study aims to explore the differences in social interaction behavior between the two. Surveys and data analysis are used in the research approach to describe growing social interaction tendencies among millennials and Gen Z.